Community composition of epiphytic diatoms on economically important seaweeds in Guiuan, Eastern Samar - Capili, Phoebie Grace R.; Yap-Dejeto, Leni G. (2024)
Epiphytic diatoms that grow on surfaces of seaweeds play a significant role in providing food supply to herbivores of coastal and shallow water ecosystems. Despite their ecological significance in the marine food web, excessive proliferation of epiphytic diatoms often leads to nutrient and light limitations that impedes growth of these seaweeds. This study assessed the community composition of epiphytic diatoms on seaweeds. This provides data of composition and abundance of diatoms epiphytic on seaweed species. Epiphytic diatoms were removed from three economically important seaweed species, Caulerpa lentillifera, Sargassum polycystum, and Kappaphycus alvarezii, collected from Guiuan, Eastern Samar. These were identified and counted under an inverted microscope. A total of 22 epiphytic diatom species were found with Navicula sp. being the most abundant diatom (25.2±1.81%), while the least abundant was Entomoneis sp. (0.02 ± 0.08%). S. polycystum had the highest number of epiphytic diatom species compared to Caulerpa lentillifera and K. alvarezii. Furthermore, S. polycystum had the highest epiphytic diatom density among all seaweeds at 1.4 ±6.1x 10 cells/g, while K. alvarezii had the lowest density at 2.8 ±0.37 x 10' cells/g. Furthermore, S. polycystum had the most diverse composition of epiphytic diatoms with an average of 2.45 ± 0.11 while K. alvarezii had the lead diversity with an average of 1.50±0.19. The abundance and composition of epiphytic diatoms on the different seaweed species in this study suggests potential growth due to surface structure, photosynthetic process, nutrient uptake, and location.
Undergraduate thesis (B.S. Biology) -- University of the Philippines, Tacloban.